Digital Libraries for Open Knowledge : 24th International Conference on Theory and Practice of Digital Libraries, TPDL 2020, Lyon, France, August 25–27, 2020, Proceedings /: 24th International Conference on Theory and Practice of Digital Libraries, TPDL 2020, Lyon, France, August 25–27, 2020, Proceedings. (2020) - Unknown
No abstract available